Risk stratification for relapsed/refractory classical Hodgkin lymphoma integrating pretransplant Deauville score and residual metabolic tumor volume. Issue 5 (23rd February 2022) - Yhim, Ho‐Young; Eshet, Yael; Metser, Ur; Lajkosz, Katherine; Cooper, Matthew; Prica, Anca; Kukreti, Vishal; Bhella, Sita; Lang, Noémie; Xu, Wei; Rodin, Danielle; Hodgson, David; et al.
Abstract: Pretransplant Deauville score (DS) is an imaging biomarker used for risk stratification in relapsed/refractory classical Hodgkin lymphoma (cHL). However, the prognostic value of residual metabolic tumor volume (rMTV) in patients with DS 4–5 has been less well characterized. We retrospectively assessed 106 patients with relapsed/refractory cHL who underwent autologous stem cell transplantation. Pretransplant DS was determined as 1–3 (59%) and 4–5 (41%), with a markedly inferior event‐free survival (EFS) in patients with DS 4–5 (hazard ratio [HR], 3.14; p = .002). High rMTV41% (rMTVhigh, ≥4.4 cm 3 ) predicted significantly poorer EFS in patients with DS 4–5 (HR, 3.70; p = .014). In a multivariable analysis, we identified two independent factors predicting treatment failure: pretransplant DS combined with rMTV41% and disease status (primary refractory vs . relapsed). These two factors allow to stratify patients into three groups with divergent 2‐year EFS: 89% for low‐risk (51%; relapsed disease and either pretransplant DS 1–3 or DS 4–5/rMTVlow ; HR 1), 65% for intermediate‐risk (28%; refractory disease and either DS 1–3 or DS 4–5/rMTVlow ; HR 3.26), and 45% for high‐risk (21%; DS 4–5/rMTVhigh irrespective of disease status; HR 7.61) groups. Pretransplant DS/rMTV41% combination and disease status predict the risk of post‐transplant treatment failure and will guide risk‐stratified approaches in relapsed/refractory cHL. Abstract :